The importance of the Amazon context in the teaching of Botany in Basic Education (Research, Society and Development, 2021)
The objective of this work was to verify the opinion of high school students (basic education) about the strategies used by Biology teachers from the state public network of Tucuruí/PA for teaching Botany in the Amazon context. Data were collected from the application of a structured questionnaire with objective questions, containing questions regarding the importance of teaching Botany, practical classes and projects carried out by schools, teaching strategies and teaching resources adopted by teachers, Botany and its relationship with environmental preservation. The analysis of the collected data proves the importance that the students give to Botany teaching linked to the preservation of the Amazon and the lack of interest in the traditional teaching method and the need for practical classes using the green areas of the Amazon forest. The results presented in this study suggest the implementation of an educational project aimed at teaching Botany in basic education schools, based on teaching strategies that emphasize the student's reality and the contextualization of the contents supported by practical classes using the resources of the regional flora.